2017
DOI: 10.1016/j.physbeh.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and gene expression alterations in a rodent model of binge eating disorder

Abstract: Binge eating disorder (BED) is defined as recurrent, distressing over-consumption of palatable food (PF) in a short time period. Clinical studies suggest that individuals with BED may have impairments in cognitive processes, executive functioning, impulse control, and decision-making, which may play a role in sustaining binge eating behavior. These clinical reports, however, are limited and often conflicting. In this study, we used a limited access rat model of binge-like behavior in order to further explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 130 publications
(126 reference statements)
2
21
0
1
Order By: Relevance
“…The intent of this approach is to ensure that the initial orientation of the animal in the maze varies randomly from trial to trial (similarly to different starting positions in the Morris water maze). For the rats, the usual experimental setup consists of two trials per day for 5 days, up to 2 or 3 min duration (Chawla et al 2017; Maegele et al 2005; Stouffer and Heisey 2013; Walesiuk and Braszko 2010). Typically for the mice, as proposed by Sunyer et al (2007), the acquisition phase consists of four sessions per day for four consecutive days.…”
Section: Bm Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The intent of this approach is to ensure that the initial orientation of the animal in the maze varies randomly from trial to trial (similarly to different starting positions in the Morris water maze). For the rats, the usual experimental setup consists of two trials per day for 5 days, up to 2 or 3 min duration (Chawla et al 2017; Maegele et al 2005; Stouffer and Heisey 2013; Walesiuk and Braszko 2010). Typically for the mice, as proposed by Sunyer et al (2007), the acquisition phase consists of four sessions per day for four consecutive days.…”
Section: Bm Proceduresmentioning
confidence: 99%
“…The first part of the BM task, i.e., the acquisition phase followed by the acquisition probe trial, allows an evaluation of spatial learning and spatial memory. This part is believed to be associated with hippocampus function (Barnes 1979; Kennard and Woodruff-Pak 2011; Negrón-Oyarzo et al 2015; Rodriguez et al 2013), while the second part of the task (i.e., reversal learning trials) allows for the evaluation of the cognitive flexibility that is associated with frontal cortex function (Crews and Boettiger 2009; Chawla et al 2017). Although BM is not as popular a task as the Morris water maze or radial arm maze, it possesses some advantages which make it a very attractive alternative, especially for the former.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, despite the higher incidence of binge eating in the female population and the established role that stress and negative affect plays in this behavior, many studies to date have used male subjects and often do not specifically examine stress‐related overeating. When a stressor is used it is often a physical stressor such as tail‐pinch or foot‐shock which does not accurately model the mode of stress experienced by human subjects (ie, emotional) . Indeed, stress‐related disorders are positively correlated with bingeing episodes and are more prevalent in females, underscoring the importance of designing ethologically relevant animal models to investigate the interplay between stress and bingeing behaviors .…”
Section: Introductionmentioning
confidence: 99%
“…When a stressor is used it is often a physical stressor such as tailpinch or foot-shock which does not accurately model the mode of stress experienced by human subjects (ie, emotional). [8][9][10][11] Indeed, stress-related disorders are positively correlated with bingeing episodes and are more prevalent in females, underscoring the importance of designing ethologically relevant animal models to investigate the interplay between stress and bingeing behaviors. [12][13][14][15] In 2009 Cifani et al reported an elegant model of emotional stress-induced binge eating in female rats where repeated cyclic caloric restriction induced binge eating of highly palatable food when exposed to a frustrative stressor.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, el GHSR es capaz de heterodimerizar con otros receptores acoplados a proteínas G y de modular la actividad de estos receptores en respuesta a sus ligandos (Wellman and Abizaid, 2015). De particular interés resulta la heterodimerización del GHSR con el receptor de dopamina D2, ya que se han reportado cambios en los niveles de expresión de este receptor en trastornos de la ingesta (Chawla et al, 2017;Rospond et al, 2019). Así, una posible vía de regulación del consumo de DACG por la actividad constitutiva del GHSR sería a través de la regulación del D2, aunque son necesarios más estudios para poner en evidencia la existencia de este fenómeno.…”
unclassified